Hubungan Antara Tingkat Depresi dengan Penurunan Kognitif pada Lansia: The Relationship Between Depression Levels and Cognitive Decline in the Elderly - Debi Nely Manurung; Maria Susila Sumartingsih; Roza Indra Yeni; Ricky Riyanto Iksan (Journal of Nursing Education and Practice, 2026)
Introduction: Elderly individuals are vulnerable to depression and cognitive decline, which can impair memory, orientation, and daily functioning, reducing quality of life. Family and community support help mitigate these effects.Objectives: This study examined the relationship between depression and cognitive decline in elderly patients at Hospital X.Method: A cross-sectional study included 55 elderly respondents selected purposively from 121 patients. Depression was measured using the Geriatric Depression Scale Short Version (GDS-SV), and cognitive function using the Mini-Mental State Examination (MMSE). Bivariate analysis with Chi-Square tested the association between depression and cognitive function.Results: Most elderly with mild to moderate depression had normal cognitive function, while those with severe depression predominantly exhibited cognitive impairment. The relationship between depression level and cognitive function was statistically significant (p = 0.004).Conclusion: Depression levels are significantly associated with cognitive decline in the elderly. Early detection of depression and cognitive stimulation are essential to prevent further cognitive deterioration. Interventions should include family- and community-based psychosocial support, cognitive stimulation, counseling, and emotional guidance. Family presence, such as living with children or relatives, serves as a protective factor for emotional stability and cognitive function. Healthcare professionals should integrate depression screening, family education, and cognitive interventions into elderly care plans to improve quality of life and independence.